Letter from Ernest Bevin to Walter Citrine, 5 May 1926, re: troop movements on City Road, London
1926-05-05 "Letter from Ernest Bevin to Walter Citrine, 5 May 1926, re: troop movements on City Road, London" [g0813001.jpg], 5 May 1926, Bevin, Ernest TUC Organisation